Azacitidine as a bridge to allogeneic hematopoietic cell transplantation in a pediatric patient with Fanconi anemia and acute myeloid leukemia. (15th December 2016) - Ding, Hilda; Hashem, Hasan; Cabral, Linda; Rangarajan, Hemalatha; Abusin, Ghada; Lazarus, Hillard M.; Abu‐Arja, Rolla
Abstract: HCT is the definitive therapy for patients with FA and AML. Conventional cytotoxic agents cause potential DNA damage, and currently, there is no established regimen for these patients prior to HCT. A 13‐year‐old male with FA and refractory AML was given azacitidine, achieved morphologic remission and underwent HCT. At 95 days after HCT, he relapsed. Azacitidine along with DLI was used as first salvage therapy. Azacitidine was overall well tolerated with minimal side effects. In patients with AML and FA, azacitidine can be considered an alternative to conventional chemotherapy.